Strategy for Handling Conflict Resolution Through a Territorial Development Approach - Suharjo, Dwi; Nur Ali, Muhammad; Hasbullah, Hasbullah (Lafadz Jaya Publisher, 2024)
The aim of this research is to analyze and understand the anatomy of social religious conflict in the Poso conflict as learning through the territorial development approach as a resolution and problem solving strategy. This research uses qualitative research. The researcher's reason is that the problem being studied is very general, dynamic and complex, not an independent reality but an object full of transcendental meaning (religious in nature and difficult to understand). This research procedure was carried out by analyzing the opinions of leadership elements in the Central Sulawesi region, including the military, Civil Officials, NGOs (NGOs) related to conflict studies, Conflict Actors, Religious Leaders, and Social Science Experts. The mediation approach was carried out through territorial guidance by the Indonesian National Land Army apparatus. The research results show that anatomically, the cause of the Poso conflict comes from within the Poso community and not external parties. The Poso conflict was caused by many factors, not only related to religious factors but also the overlap of various factors, such as economic inequality, political institutional crisis, distrust in legal institutions and law enforcement, security crisis and disorientation of socio-cultural values. The resolution is carried out through the territorial development approaches such as (1) the territorial development in the Field of Ideology. (2) the territorial development in the Political Sector which is directed and implemented through non-physical activities, (3) the territorial development through an Economic Sector approach. (4). the territorial development through a Socio-Cultural Sector approach. which is directed at developing community aspects of culture and social ethics. (5) Special Assistant in the Field of Defense and Security. which is directed at community development in the field of public security defense. Based on the research results, it is recommended to central and regional leaders that the Poso Complex should be used as an event for valuable learning and serious understanding of conflict triggers (triggers), basic causes of conflict (pivotal factors), factors that mobilize conflict (mobilizing factors), as well as factors which exacerbate the conflict (aggravating factors). Then it is recommended that the TNI be able to carry out intensity and existence as well as professionalism of territorial development by Indonesian National Army officers from the army headquarters in their subordinate units such as military area commands, military resort commands, and military district commands and their staff to be able to detect symptoms of more vital factors. early so that the symptoms of conflict can be controlled.